Utilizing Game Based Applications for Teaching Historical Content - Khaeru Alfi Syahr; Yusuf Hendra Pratama; Asno Azzawagama Firdaus (Universitas Islam Al-Azhar Mataram, 2025)
This research investigates the integration of game-based applications as an instructional medium for conveying historical content within educational contexts. With the rapid advancement of digital technologies, interactive learning platforms such as educational games are becoming increasingly prominent in classroom environments to foster deeper student engagement and understanding. History, which is traditionally regarded as a static and memorization-heavy subject, is being reimagined through the use of interactive digital media that incorporates visual storytelling, narrative design, and dynamic challenges, thereby offering a more experiential learning process. Employing a qualitative descriptive methodology, the study synthesizes insights from literature reviews and participatory observations of various game-based educational tools centered on Indonesian historical themes. Among the platforms examined are Wordwall, Android-based applications focusing on the Indonesian independence movement, and narrative-driven games introducing national heroes and ancient kingdoms. The findings reveal that these digital interventions not only enhance learner motivation but also contribute to improved cognitive retention and active classroom participation. The implementation of Wordwall in high school settings, for example, demonstrates measurable benefits in engagement through gamified quiz formats. Despite these advantages, notable barriers persist. Limited access to necessary technological infrastructure and the need to ensure historical accuracy in digital content remain critical issues. Consequently, interdisciplinary collaboration particularly involving historians, educators, and game developers is crucial to maintaining the pedagogical and factual integrity of these tools. In summary, the utilization of educational games represents a transformative approach to history instruction. By blending technology with pedagogy, such applications enable educators to deliver historical narratives in a manner that is not only academically rigorous but also engaging and meaningful for today’s digital-native learners.